An Analysis of the Language Style Used by Barrack Obama and Michelle Obama in Oprah Winfrey Show - Difta Anggraini; Sudiran Sudiran (University of Muhammadiyah Malang, 2014)
An Analysis of the Language Style Used by Barrack Obama and Michelle Obama in Oprah Winfrey Show